Hofmeister effects of anions on the kinetics of partial reactions of the Na+,K+-ATPase. - Ganea, C (1999)
The effects of lyotropic anions, particularly perchlorate, on the kinetics of partial reactions of the Na+,K+-ATPase from pig kidney were investigated by two different kinetic techniques: stopped flow in combination with the fluorescent label RH421 and a stationary electrical relaxation technique. It was found that 130 mM NaClO4 caused an increase in the Kd values of both the high- and low-affinity ATP-binding sites, from values of 7.0 (+/- 0.6) microM and 143 (+/- 17) microM in 130 mM NaCl solution to values of 42 (+/- 3) microM and 660 (+/- 100) microM in 130 mM NaClO4 (pH 7.4, 24 degrees C). The half-saturating concentration of the Na+-binding sites on the E1 conformation was found to decrease from 8-10 mM in NaCl to 2.5-3.5 mM in NaClO4 solution. The rate of equilibration of the reaction, E1P(Na+)3 left arrow over right arrow E2P + 3Na+, decreased from 393 (+/- 51) s-1 in NaCl solution to 114 (+/- 15) s-1 in NaClO4. This decrease is attributed predominantly to an inhibition of the E1P(Na+)3 --> E2P(Na+)3 transition. The effects can be explained in terms of electrostatic interactions due to perchlorate binding within the membrane and/or protein matrix of the Na+,K+-ATPase membrane fragments and alteration of the local electric field strength experienced by the protein. The kinetic results obtained support the conclusion that the conformational transition E1P(Na+)3 --> E2P(Na+)3 is a major charge translocating step of the pump cycle.